Evaluation of the biocompatibility of silicone gel implants - histomorphometric study - França, Diurianne Caroline Campos [UNESP]; Castro, Alvimar Lima de [UNESP]; Soubhia, Ana Maria Pires [UNESP]; Aguiar, Sandra Maria Herondina Coelho Ávila de [UNESP]; Goiato, Marcelo Coelho [UNESP] (ScopeMed, 2013)
Breast implants are medical devices that are used to augment breast size or to reconstruct the breast following mastectomy or to correct a congenital abnormality. Breast implants consist of a silicone outer shell and a filler (most commonly silicone gel or saline). Approximately 5 to 10 million women worldwide have breast implants. Histomorphometric study to evaluate the biological tissue compatibility of silicone implants suitable for plastic surgery and the adverse effects and risks of this material. Thirty Wistar white rats received subcutaneous implants and the revestiment of silicone gel Silimed ®®, and randomized into six groups of five animals each, according to the type of implanted material and the time of sacrifice. Eight areas of 60.11mm2 corresponding to the obtained surgical pieces were analyzed, counting mesenchymal cells, eosinophils, and foreign body giant cells, observing an acceptable biocompatibility in all implants, for subsequent statistical analysis by Tukey test. Silicone gel showed inflammation slightly greater than for other groups, with tissue reactions varying from light to moderate, whose result was the formation of a fibrous capsule around the material, recognized by the organism as a foreign body. Despite frequent local complications and adverse outcomes, this research showed that the silicone and top layer presented an acceptable chronic inflammatory reaction, which did not significantly differ from the control group. In general, it is possible to affirm that silicone gel had acceptable levels of biocompatibility, confirmed the rare presence of foreign body giant cells, and when of the rupture, formed a fibrous capsule around the material, separating the material of the organism. © AVICENA 2013.
Keywords: Breast Implantation; Materials Testing; Rats; Silicone Gels; Wistar; silicone gel; adverse outcome; animal experiment; animal tissue; biocompatibility; controlled study; eosinophil; evaluation; fibroblast; giant cell; histocompatibility; inflammation; inflammatory cell; inflammatory infiltrate; morphometrics; nonhuman; plastic surgery; qualitative analysis; rat; risk assessment; silicone prosthesis; tissue reaction